Fig: A fruit for health - Vishwakarma, Pradeep Kumar; Kanade, Nandkishor M; Singh, Dharmpal; Kaushal, Ashish (Indian Horticulture, 2021)
Fig is grown in many parts of the world with moderate climate. Figs are eaten dry and fresh both, as fresh figs are highly perishable, so fresh figs are consumed only in nearer market but dry figs are exported for long distance markets. Fresh and dry both fruits are rich in fibre; potassium, calcium, and iron. Fresh figs are highly sensitive to physical damage, and susceptible to disease and infections. Preharvest and postharvest conditions are very important to improve fruit quality and postharvest life. Due to its nutritional quality, fresh fruit breeders are taking it as a challenge for development of new improved varieties for long shelf life of fresh fruits.